Controlled Induction of Parthenogenesis in Transgenic Rice via Post-translational Activation of PsASGR-BBML - Sidhu, Gurjot Singh; Conner, Joann A.; Ozias-Akins, Peggy (Frontiers in Plant Science, 2022)
Modern plant breeding programs rely heavily on the generation of homozygous lines with the traditional process requiring inbreeding of a heterozygous cross for five to six generations. Doubled haploid (DH) technology, a process of generating haploid plants from an initial heterozygote, followed by chromosome doubling, reduces the process to two generations. Currently established in vitro methods of haploid induction include androgenesis and gynogenesis while in vivo methods are based on uni-parental genome elimination. Parthenogenesis, embryogenesis from unfertilized egg cells, presents another potential method of haploid induction. PsASGR-BBML, an AP2 transcription factor, induces parthenogenesis in a natural apomictic species, Pennisetum squamulatum (Cenchrus squamulatus) and PsASGR-BBML transgenes promote parthenogenesis in several crop plants. The dominant nature of PsASGR-BBML transgenes impedes their use in DH technology. Using a glucocorticoid based post-translational regulation system, PsASGR-BBML can be regulated at the flowering stage to promote parthenogenesis. Conditional expression presents a novel opportunity to use parthenogenetic genes in DH production technology and to elucidate the molecular mechanism underlying parthenogenetic embryogenesis.